Privacy Albeit Late - Rauber, Gustavo; Almeida, Virgílio A. F.; Kumaraguru, Ponnurangam (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
Online Social Networks (OSNs) such as Facebook and Twitter have experienced exponential growth in recent years. Users are spending more time on OSNs than on any other sites and services on the Internet. Users post and share a lot of personal information on these sites without being aware of privacy implications or simply not caring much about them, what turns to be a treasure for marketing companies and cybercriminals. Characterizing the privacy awareness of users is important to design technologies and policy solutions. Users expect the OSN to provide good privacy protection or controls so they can make informed decisions about their privacy. This paper investigates the privacy awareness of users on Facebook using real-world data (not self reported). The main findings are: only a low percentage of users change the default privacy settings; a large percentage of users expose their gender publicly; women are more concerned about disclosing personal information online; many users share their photo albums and links (content) to everyone; users exercise more control over content that are more potentially dangerous to their reputation. The present study is one of the first to characterize the privacy awareness on OSN through a real world experiment. Implications of the study are discussed.